RADIOGRAPHIC STUDY OF THE MEDIAL JOINT SPACE OF THE HIP IN LEGG-CALVÉ-PERTHES DISEASE - RENE DUJARDIN; DIEGO PRAXEDES DE MIRAS; CAIO FALK GIANNOTTI; ROBERTO BEZERRA NICOLAU; EIFFEL TSUYOSHI DOBASHI (Acta Ortopédica Brasileira, 2022)
ABSTRACT Objective: To evaluate medial joint space in affected and normal contralateral hips in patients with Legg-Calvé-Perthes disease (LCPD). Methods: To compare joint space, femoral head extrusion (FHE), medial space coefficient (MSC) of the hip, and femoral head width (FHW) in affected and normal hips, using 127 radiographs of patients with unilateral LCPD and considering age groups under and over six years old as well as their disease stage. Results: No statistically significant differences were observed regarding MSC between normal and affected hips regardless of disease staging. However, medial joint distance was significantly greater in affected hips than in normal hips. In the necrosis and fragmentation phase, distance from medial space in affected hips was significantly greater than in contralateral normal hips. Comparing only affected hips, MSC and FHW showed statistically significant differences and the group > 6 yo presented higher values. Among normal hips, the group < 6 yo presented a statistically significant difference considering the MSC and FHW. Conclusions: No statistically significant difference was found between the medial joint space of affected and normal hips, except for early stages of the disease (necrosis and fragmentation). The isolated use of radiographic study is insufficient in LCPD and the lack of complementation with other exams, such as magnetic resonance, can delay diagnosis of and onset of treatment for the disease. Level of Evidence III, Study of Non Consecutive Patients; without Consistently Applied Reference “Gold” Standard.